INFLUENCE OF BRAND IMAGE ON THE WORD OF MOUTH WHICH IMPLICATES TO BRAND EQUITY SPORT EVENT SRIWIJAYA RANAU GRAN FONDO 2022 - Ahmad Kurniawan; Rini Andari; Caria Ningsih (Bajang Institute, 2023)
There is a change in consumer behavior from the pandemic to the pandemic transition that affects the brand equity sport event Sriwijaya Ranau Gran Fondo 2022, thus making researchers analyze the extent to which the relationship between brand image factors includes brand congruence, brand trust, brand commitment, to word of mouth which has implications for brand equity sport event can affect the behavior of consumers or participants. Using a quantitative research method with a descriptive and survey research design using a sample of 353 respondents from the participants present, then analyzed using quantitative descriptive statistical analysis and structural equation model (SEM) analysis. The results showed that there was a significant effect of brand congruence on brand trust, there was a positive relationship between brand congruence and brand commitment, a positive direct effect of brand trust on brand commitment, there was no significant relationship between brand trust and word of mouth, there was an influence between brand commitment on word of mouth, and there is a significant strong relationship between word of mouth and brand equity. Thus it has implications for sport event organizers to continue to increase the satisfaction and comfort of consumers or attendees, as well as correcting deficiencies in values that do not meet the needs of consumers or participants in order to develop a very good sports event brand image.